Reactive Oxygen Species-Responsive Nanococktail With Self-Amplificated Drug Release for Efficient Co-Delivery of Paclitaxel/Cucurbitacin B and Synergistic Treatment of Gastric Cancer - Pang, Lijun; Zhang, Lei; Zhou, Hong; Cao, Ling; Shao, Yueqin; Li, Tengyun (Frontiers in Chemistry, 2022)
Application of drug combinations is a powerful strategy for the therapy of advanced gastric cancer. However, the clinical use of such combinations is greatly limited by occurrence of severe systemic toxicity. Although polymeric-prodrug-based nanococktails can significantly reduce toxicity of drugs, they have been shown to have low intracellular drug release. To balance between efficacy and safety during application of polymeric-prodrug-based nanococktails, a reactive oxygen species (ROS)-responsive nanococktail (PCM) with self-amplification drug release was developed in this study. In summary, PCM micelles were co-assembled from ROS-sensitive cucurbitacin B (CuB) and paclitaxel (PTX) polymeric prodrug, which were fabricated by covalently grafting PTX and CuB to dextran via a ROS-sensitive linkage. To minimize side effects of the PCM micelles, a polymeric prodrug strategy was employed to prevent premature leakage. Once it entered cancer cells, PCM released CuB and PTX in response to ROS. Moreover, the released CuB further promoted ROS generation, which in turn enhanced drug release for better therapeutic effects. In vivo antitumor experiments showed that the PCM-treated group had lower tumor burden (tumor weight was reduced by 92%) but bodyweight loss was not significant. These results indicate that the developed polymeric-prodrug, with a self-amplification drug release nanococktail strategy, can be an effective and safe strategy for cancer management.